The Effect of Job Characteristics on Employee Satisfaction at the Education Office of Riau Archipelago Province - Reza, Amru; Subiyakto, Rudi; Adhayanto, Oksep (Publikasi Indonesia, 2022)
Every job has certain characteristics or aspects that accompany individuals in carrying out their work. These aspects can make individuals work well or vice versa. Job characteristics as identification of various dimensions contained in a job design that simultaneously improves organizational efficiency and employee satisfaction. Job satisfaction is one of the ways that companies do to improve employee performance, companies are unlikely to achieve goals properly if employees are not likely to achieve goals properly if employees do not get good job satisfaction. The research method in this research is descriptive qualitative. This type of research is quantitative, with a sample of 173 respondents. The purpose of this study was to determine the effect of job characteristics on employee job satisfaction at the Riau Islands Province Education Office. Based on the tests carried out on the results of research and discussion, it can be seen that Job Characteristics have a positive and significant influence on Job Satisfaction. This certainly gives an indication that the increase in Job Characteristics will have a significant effect on increasing employee job satisfaction at the Riau Islands Province Education Office. The percentage of influence given by Job Characteristics to Job Satisfaction based on the results of data processing with an r square value of 13.5%.